Views of Makerere University Radiography Students in Third and Fourth Year on the Implementation of Internship after Accomplishing their Four-Year Bachelors’ Degree. - Lado, Taji Evelyne; Bwangu, John; Murachi , Eric (Journal of Education and Practice, 2026)
Purpose: The study purposed to find out the views of the third and fourth-year Radiography students at Makerere University, College of health sciences on the implementation of internship after their four-year bachelors’ degree since they currently do not have internship as part of their programme, despite the fact that other medical courses such as Medicine and Surgery have an ongoing internship programme. Methodology: A descriptive quantitative cross-sectional study was carried out using a convenience sampling method to find out the views of Makerere University radiography students in third and fourth year on the implementation of internship after accomplishing their four-year bachelors’ degree. The data was collected from 27 respondents who were purposely selected by the researcher through a self-developed structured questionnaire and analyzed using Microsoft Excel programme. Findings: The study revealed that 100% of the students were aware of internship and 60% of the respondents believed that internship was important after completion of the undergraduate studies. Despite the fact that the majority (60%) of the respondents acknowledged that internship was important, a few (35%) wanted internship to be part of the undergraduate programme while the majority (65%) did not want it to be part. The research further showed that 35% of the students were undecided on the importance of internship after completion of the undergraduate studies in Radiography. A paltry 5% said it was not necessary because Radiography is a practical course therefore, there is no need for an internship and that it would promote laziness among the students. The study revealed mixed results including; awareness, knowledge level, and interest. Unique Contribution to Theory, Practice and Policy: This study highlighted the necessity of a structured, post-classroom active experimentation to bridge the gap between theoretical knowledge and professional practice as well as enhance the performance of the outgoing students. The study findings recommended Makerere University College of Health Sciences (MAKCHS), Ministry of Health and the board of Radiographers in Uganda to provide annual awareness sessions on internship, include post Radiography students in the government payroll and also carryout different consultations from the seniors in the profession on the need of internship for the Bachelor’s degree of radiography at Makerere University.